2007
DOI: 10.1152/ajpregu.00171.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of weight loss and weight regain mechanisms after Roux-en-Y gastric bypass in rats

Abstract: Y gastric bypass (RYGB) is the most effective therapy for morbid obesity, but it has a ϳ20% failure rate. To test our hypothesis that outcome depends on differential modifications of several energy-related systems, we used our established RYGB model in Sprague-Dawley diet-induced obese (DIO) rats to determine mechanisms contributing to successful (RGYB-S) or failed (RYGB-F) RYGB. DIO rats were randomized to RYGB, sham-operated Obese, and sham-operated obese pair-fed linked to RYGB (PF) groups. Body weight (BW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
58
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 82 publications
14
58
1
1
Order By: Relevance
“…Mortality rates for gastric bypass models in rats are rarely reported and range from 0% to 30% [7,8,[11][12][13][14][15][16][17][18]. Thus, our rate is within the reported range.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Mortality rates for gastric bypass models in rats are rarely reported and range from 0% to 30% [7,8,[11][12][13][14][15][16][17][18]. Thus, our rate is within the reported range.…”
Section: Discussionsupporting
confidence: 72%
“…Given the rapid increase in gastric bypass procedures, it is important to understand the underlying mechanisms by which gastric bypass induces and sustains weight loss [6]. The use of animal models for gastric bypass surgery is a valuable tool and has been shown to be a valid model to mimic human weight loss after gastric bypass [7][8][9][10]. However, there is a great variety in different techniques being used and results in weight loss and food intake as well as mortality rates are heterogeneous [7,8,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear how the leptin set point may be reset. An increased leptin receptor expression in the rat hypothalamus after GBP may partly have a role, 40 but other changes including a higher affinity of these receptors may also account for these observations. 43 A second potential mechanism, the 'starvation response' opposing weight loss, usually triggered by lower leptin levels, is overridden by increased gut hormones such as PYY levels.…”
Section: Experimental Datamentioning
confidence: 95%
“…9,37,38 These findings are in line with previous reports demonstrating a reduced body weight without decreased food intake or malabsorption, but increased energy expenditure after GBP in rats. 39,40 Furthermore, Stylopoulos et al 41 described a 19% increase in total and a 31% increase in resting energy expenditure in rats after GBP operation. The authors concluded that these effects, along with a 17% decrease in food intake and a 4% decrease in nutrient absorption, account for the normalization of body weight after GBP.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation